METTL3 Contributes to Osteosarcoma Progression by Increasing DANCR mRNA Stability via m6A Modification - Zhou, Xinying; Yang, Yang; Li, Yuejun; Liang, Guojun; Kang, Dawei; Zhou, Bing; Li, Qingchu (Frontiers in Cell and Developmental Biology, 2022)
Background: Osteosarcoma (OS) is the most prevalent bone cancer among children and adolescents, with relatively high mortality rates. RNA N6-methyladenosine (m6A) is the most common human mRNA modification with diverse functions in a variety of biological processes. Previous studies indicated that methyltransferase-like 3 (METTL3), the first methyltransferase to be identified, acted as an oncogene or tumor suppressor in multiple human cancers. However, its functions and underlying mechanisms in OS progression remain unclear; therefore, we explored these processes. Methods: We used real-time quantitative PCR (RT-qPCR) and Western blot assays to explore METTL3 expression in OS tumor tissues and five OS cell lines to assess its clinical significance. To further examine the functional role of METTL3 during OS progression, CCK-8 analyses, transwell assays, and xenograft model studies were conducted after silencing METTL3. Additionally, underlying mechanisms were also explored using RIP-seq and RIP-qPCR approaches. Results: METTL3 was upregulated in OS tumor tissues and cell lines and was associated with a worse prognosis. Moreover, METTL3 silencing suppressed OS cell proliferation, migration, and invasion. Also, in vivo METTL3 oncogenic functions were confirmed in the xenograft model. Comprehensive mechanistic analyses identified long non-coding RNA (lncRNA) DANCR as a potential target of METTL3, as indicated by reduced DANCR levels after METTL3 silencing. Also, lncRNA DANCR knockdown repressed OS cell proliferation, migration, and invasion. Furthermore, both METTL3 and lncRNA DANCR silencing significantly suppressed OS growth and metastasis. Finally, we hypothesized that METTL3 regulated DANCR expression via m6A modification-mediated DANCR mRNA stability. Conclusion: METTL3 contributes to OS progression by increasing DANCR mRNA stability via m6A modification, meaning that METTL3 may be a promising therapeutic target for OS treatment.